2016
DOI: 10.1177/0044118x14528958
|View full text |Cite
|
Sign up to set email alerts
|

The Code of Silence in Schools

Abstract: Socio-ecological models of victimization reporting incorporate normative constraints and instrumental considerations at the individual and contextual levels. Drawing on this model, we explore factors related to students' willingness to report problem behaviors that they might observe in school. Data obtained from student and teacher/administrator surveys and administrative data are used to explore these relationships. We find that individual-level factors are the primary determinants of reporting attitudes, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…In accordance with hypotheses 2.1 to 2.3 and along the lines of findings in previous research, our results confirm that misbehaviour perceived by teachers is reduced with three important measures to improve school climate: fairness of rules and discipline (Gottfredson et al, 2005;Morrison, 2018;Slocum et al, 2017;Way, 2011); family support for teachers (Sheldon & Epstein, 2002;Skaalvik et al, 2009); and better leadership from school principals, which encourages participation in school decisions by teachers -as is already the case in the majority of centres -but also by students and families, which few schools promote (Bowen et tal., 2006;Hopson & Lee, 2011;OECD, 2014OECD, , 2016Thapa et al, 2013;Tickle et al, 2011).…”
Section: Misbehaviour Based On School Characteristicssupporting
confidence: 91%
See 3 more Smart Citations
“…In accordance with hypotheses 2.1 to 2.3 and along the lines of findings in previous research, our results confirm that misbehaviour perceived by teachers is reduced with three important measures to improve school climate: fairness of rules and discipline (Gottfredson et al, 2005;Morrison, 2018;Slocum et al, 2017;Way, 2011); family support for teachers (Sheldon & Epstein, 2002;Skaalvik et al, 2009); and better leadership from school principals, which encourages participation in school decisions by teachers -as is already the case in the majority of centres -but also by students and families, which few schools promote (Bowen et tal., 2006;Hopson & Lee, 2011;OECD, 2014OECD, , 2016Thapa et al, 2013;Tickle et al, 2011).…”
Section: Misbehaviour Based On School Characteristicssupporting
confidence: 91%
“…However, when family support was low, disruption was greater (or lesser) as students' perception of coercive treatment from teachers increased (or decreased). These results coincide with those obtained in the majority of research published in recent decades in this area regarding the role of coercion, which has reported that not only does coercion frequently not reduce misbehaviour levels; it even increases them (Demanet et al, 2012;Jennings et al, 2009;Morrison, 2018;Slocum et al, 2017;Wallace et al, 2014;Sun, 2015;Wang & Degol, 2016).…”
Section: Article In Presssupporting
confidence: 90%
See 2 more Smart Citations
“…Although students often have information about a potential threat at school (Daniels et al, 2010; O’Toole, 2000; Pollack, Modzeleski, & Rooney, 2008; Vossekuil, Fein, Reddy, Borum, & Modzeleski, 2002), students who know about a threat may not report it or may only do so only if they personally experience a direct threat (Madfis, 2014). Furthermore, students’ capitulation to “negative” peers or a “street code,” and fear of retaliation or stigma of tattling, support a persistent “code of silence” that discourages reporting (Brank et al, 2007; Halbig, 2000; Madfis, 2014; Morris, 2010; Nekvasil & Cornell, 2012; Slocum, Esbensen, & Taylor, 2017).…”
Section: Introductionmentioning
confidence: 99%